Diagnostic value of electrocardiographic markers of left bundle branch block in predicting left ventricular reverse remodeling in patients receiving cardiac resynchronization therapy - L. M. Malishevsky; V. A. Kuznetsov; V. V. Todosiychuk; N. E. Shirokov; D. S. Lebedev (Российский кардиологический журнал)
Aim. To analyze the prognostic value of 18 electrocardiographic (ECG) markers of left bundle branch block (LBBB) in predicting left ventricular (LV) reverse remodeling in patients receiving cardiac resynchronization therapy (CRT).Material and methods. The study included 98 patients. Depending on the presence of reverse remodeling during CRT, defined as a decrease in LV endsystolic volume ≥15%, the patients were divided into two groups: non-responders (n=33) and responders (n=65). We selected and analyzed 18 ECG markers included in 9 LBBB criteria.Results. Among the ECG markers significantly associated with reverse remodeling during CRT, the absence of q wave in leads V5-V6 demonstrated the highest sensitivity (92,31%), a negative predictive value (70,59%) and overall accuracy (73,47%). Normal internal deviation interval of the R wave in leads V1-V3 was also associated with the best sensitivity (92.31%), while QS with a positive T in lead aVR — the best specificity (69,7%). Discordant T wave demonstrated the highest positive predictive value (80,33%). Multivariate analysis revealed following ECG signs independently associated with reverse remodeling during CRT: QRS complex duration (odds ratio (OR)=1,022; 95% confidence interval (CI): 1,001-1,043; p=0,040); absence of q wave in leads V5-V6 (OR=4,076; 95% CI: 1,071-15,51; p=0,039); discordant T wave (OR=4,565; 95% CI: 1,708-12,202; p=0,002). These ECG findings were combined into a mathematical model that demonstrated high predictive power (AUC=0,81 [0,722-0,898], p<0,001). Once the cut-off point was determined, a binary variable was obtained that showed higher sensitivity, negative predictive value, and overall accuracy when compared with the actual LBBB criteria. The 5-year survival rate among patients with a model value above the cut-off point was 84,4%, while in patients with a value below the cut-off point — 50% (Log-rank test, p=0,001). To improve usability of the model, a mobile application was developed.Conclusion. For the first time, the diagnostic value of ECG markers of LBBB were analyzed and a mathematical model with ECG signs was proposed to predict reverse remodeling in patients receiving CRT.